Intra-articular hyaluronan injections in the treatment of osteoarthritis of the knee: a randomised, double blind, placebo controlled multicentre trial. Hyaluronan Multicentre Trial Group. - Lohmander, L S (1996)
OBJECTIVE: To assess the effects of intra-articular injections of hyaluronan on symptoms of knee osteoarthritis (OA). METHODS: Two hundred and forty patients with symptomatic, radiological knee OA were randomly assigned to treatment with weekly injections for five weeks with either 25 mg of high molecular weight hyaluronan or vehicle. Results were evaluated at weeks 1, 2, 3, 4, 5, 13, and 20 by visual analogue scales (pain, function, motion, activity), algofunctional index, and global evaluation by patient and investigator. Analysis was by "intention to treat', "per protocol', and area under the curve principles on unstratified patient groups and for patients stratified into four groups of equal size by age and baseline algofunctional index. RESULTS: No serious side effects were reported. At 20 weeks both treatment groups were improved compared with baseline, with no difference between unstratified groups treated with placebo or hyaluronan. Comparison of treatment groups stratified by age and baseline algofunctional index revealed a significant difference in favour of hyaluronan over placebo (pain, activity, algofunctional index, global evaluations by patient and investigator) for patients older than 60 years and with a baseline algofunctional index greater than 10. There was no clinically relevant difference between the two treatments for the other three stratified subgroups of younger age or fewer symptoms. Similar results were obtained by area under the curve, intention to treat, and per protocol analysis. CONCLUSIONS: Patients older than 60 years with knee osteoarthritis and with significant symptoms corresponding to an index of severity of knee disease of 10 or more, comprise the group most likely to benefit from treatment with intra-articular hyaluronan injections.